PENGARUH SISTEM OLAH TANAH TERHADAP TOTAL BAKTERI TANAH PADA PERTANAMAN KEDELAI MUSIM TANAM KEDUA SETELAH PERTANAMAN JAGUNG DI LAHAN BEKAS ALANG-ALANG (Imperata cylindrica. L) - Ardy Mahendra Saragih; Dermiyati Dermiyati; Henrie Buchari; M. A. Syamsul Arif (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2015)
This study aims to determine the effect of tillage systems on Imperata grasslands are used as a soybean crop after the second growing season maize to total soil bacteria. The research this performed using by randomized block design (RBD) with three treatments tillage systems namely: TOT = No Tillage, OTM = Minimum Tillage, OTI = Intensive Tillage, with six replications. Soil samples were taken two weeks before tillage, one day after tillage, vegetative the maximum, and one day before harvest soybean plants. Soybean crop is used as an indicator of response to the treatment applied. The data obtained were tested homogeneity with Bartlett test and additivity tested by Tukey’s test. Test the correlation between the main variables of total soil bacteria with supporting variable pH, C-organic, N-total, temperature, and soil moisture. Data were analyzed by analysis of variance followed by LSD test 5%. Tillage treatments were not significantly different to the total bacteria in the soil two weeks before the observation tillage, one day after tillage, vegetative period and the maximum one day before harvest soybean plants. There is a correlation between soil pH (HO) with total soil bacteria in the observation of one day before harvest soybean plants.